Approximate blast movement modelling for improved grade control. Issue 3 (3rd July 2019) - Vasylchuk, Y.V.; Deutsch, C.V.
ABSTRACT: An optimization algorithm has been developed to model blast-induced displacement of rock in 3-D using gridded pre- and post-blast topography and direct blast movement measurements. The blast movement problem is expressed as an optimization assignment problem. The optimization assignment problem is solved by a heuristic algorithm offering an approximate solution in a reasonable time. The objective function and optimization details are explained. An example demonstrates the steps required to model blast movement. A realistic blast movement model improves grade control by allowing better positioning of dig lines and more correct determination of the correct destination for mined rock. The algorithm is suitable for mapping pre-blast grades, categories, expected profit, or other information onto the post-blast configuration of the muckpile.